Prevalence of Pregnancy Tumor in Tripoli, Libya: A Multicenter Cross-Sectional Study - Raja Barioun; Dunya Ben Sofia; Asmaa Shanab (Khalij-Libya Journal of Dental and Medical Research, 2024)
Background and objectives. Pyogenic granuloma (pregnancy tumor) is one of the gingival inflammatory changes with an increased incidence during pregnancy. The present study aimed to determine the prevalence and characteristics of pregnancy tumors in pregnant Libyan women in Tripoli, Libya. Methods. In this descriptive cross-sectional study, pregnant Libyan women were assessed at the National Heart Center-Tajoura, Jalaa Maternity Hospital, and Tripoli University Hospital during the period from August to November 2023. Data were collected through interviewing and clinical examination of the participants and filling out a data form. Results. During four months period, of 402 pregnant Libyan women, 4 (1.0%) were clinically diagnosed with pregnancy tumors. The four cases were in their third trimester of pregnancy. Half (50%) of pregnancy tumor cases were more than 30 years old, and the other half (50%) were early 20 years old. The gingiva was the only site of the lesions, and were observed equally in the maxilla and the mandible. All pregnancy tumor cases have calculus on their teeth, bleeding gums, and poor oral hygiene status. All lesions were sessile had lobulated surfaces, and showed spontaneous and provoked bleeding. Conclusions. Although the results of this study indicate that the prevalence of pregnancy tumors in pregnant Libyan women is considered low (1.0%), oral health education programs are very important during pregnancy, and if pregnant women notice any abnormal growth during pregnancy in their mouth, they should consult a dentist. الخلفية والأهداف: الورم الحبيبي القيحي (ورم الحمل) هو أحد التغيرات الالتهابية اللثوية الذي يزداد حدوته أثناء الحمل. تهدف الدراسة الحالية إلى تحديد مدى انتشار وخصائص أورام الحمل لدى النساء الليبيات الحوامل في طرابلس، ليبيا. الطريقة: في هذه الدراسة الوصفية المقطعية، تم تقييم النساء الليبيات الحوامل في المركز الوطني للقلب - تاجوراء ومستشفى الجلاء للولادة ومستشفى طرابلس الجامعي خلال الفترة من أغسطس إلى نوفمبر 2023. تم جمع البيانات من خلال إجراء المقابلات والفحص السريري للمشاركات وملء نموذج البيانات. النتائج: خلال فترة أربع أشهر، من بين 402 امرأة ليبية حامل، تم تشخيص 4 حالات (1.0٪) سريريا بأورام الحمل. وكانت الحالات في الثلث الثالث من الحمل. كان نصف (50٪) الحالات عمرهن أكثر من 30 عاما، والنصف الآخر (50٪) كان عمرهن في أوائل 20 عاما. كانت اللثة هي الموقع الوحيد للورم. ولوحظ بالتساوي في الفك العلوي والفك السفلي. جميع حالات أورام الحمل لديها ترسبات على أسنانهن، ونزيف اللثة وحالة نظافة الفم سيئة. جميع حالات ورم الحمل كانت لها أسطح مفصصة، وأظهرت نزيفا عفويا ومستثار. الخلاصة: على الرغم من أن نتائج هذه الدراسة تشير إلى أن انتشار أورام الحمل لدى النساء الليبيات الحوامل يعتبر منخفضا (1.0٪)، إلا أن البرامج التثقيفية على صحة الفم مهمة جدا أثناء الحمل، وإذا لاحظت النساء الحوامل أي نمو غير طبيعي أثناء الحمل في فمهن، فعليهن استشارة طبيب الأسنان.